Evaluasi Penurunan Emisi Karbon melalui Pemanfaatan Panel Surya Berbasis Pedoman Intergovernmental Panel on Climate Change (IPCC) di Kawasan Industri Cikarang Bekasi: Indonesia - Pramono, Ujang; Cahyanto, Aris Dwi; Sari, Putri Anggun; Ilyas, Nur Ilman; Trialfhianty, Tyas (Jurnal Sains & Teknologi Lingkungan, 2026)
Carbon dioxide (CO₂) emissions from the energy sector are a major contributor to global warming, thus becoming a serious challenge in achieving sustainable development. Most industrial areas in Indonesia still rely on electricity supply from natural gas-fired Steam Power Plants (PLTU) which contribute to carbon emissions. Based on these problems, this study aims to: (1) evaluate the existing conditions of the integration of Solar Power Plants (PLTS) with Private Power Generation systems, (2) calculate the potential CO₂ emission reduction from the use of PLTS, and (3) analyze the Economic Value of Carbon (NEK) based on national policies. The method used refers to the 2006 Intergovernmental Panel on Climate Change (IPCC) guidelines with a Tier 2 approach, as well as NEK calculations based on the Regulation of the Minister of Energy and Mineral Resources (Permen ESDM) No. 16 of 2022. The results of the study show that the current PLTS integration uses an On-Grid system with a capacity of 30% of the connected capacity. This condition causes the emission reduction achieved to be still limited due to regulatory restrictions. To achieve optimal emission reductions, a transition to an off-grid system is necessary. The economic value of carbon from solar power plant utilization shows a surplus of IDR 812,463,000 per year. Further research is recommended to examine hybrid system scenarios, long-term economic analysis, and the impact of carbon incentive policies on accelerating renewable energy adoption in the industrial sector.